Ultrasound diagnosis of fetal hypospadias: Accuracy and outcomes. Issue 5 (October 2017) - Epelboym, Yan; Estrada, Carlos; Estroff, Judy
Summary: Objectives: The purpose of this study was to assess the positive predictive value of a prenatal ultrasound diagnosis of hypospadias when compared with postnatal diagnosis based on physical exam. Methods: We retrospectively identified all pregnant women between 2004 and 2014 who were either referred to our fetal care center carrying a fetus with an ultrasound diagnosis of possible hypospadias or who had a new diagnosis of hypospadias after imaging in our center. Results: A total of 32 cases of possible hypospadias were identified, with our fetal center ultrasound suggesting hypospadias in 25 of the 32 cases (78%). Of the 25 cases, 18 infants were confirmed to have hypospadias on postnatal physical exam (Table ), reflecting a positive predictive value of 72%. Twenty-one of twenty-five cases with suggested hypospadias on ultrasound were found to have either hypospadias or another penile anomaly on postnatal physical exam, reflecting a positive predictive value for any genital anomaly of 84%. Infants with confirmed hypospadias often had several associated GU anomalies on postnatal clinical exam. Conclusions: Our single center experience with the fetal ultrasound diagnosis of hypospadias demonstrates a high positive predictive value for a penile anomaly (21/25, 84%), and a moderately high positive predictive value for the specific diagnosis of hypospadias (18/25, 72%) when compared with the postnatal diagnosis. Table Diagnosis of hypospadias by fetal ultrasound versus physical exam. Case Fetal ultrasound diagnosis of hypospadias a Physical exam diagnosis of hypospadias a Classification of hypospadias b Other genitourinary findings 1 + + Proximal Severe chordee, penoscrotal transposition 2 + + Proximal Moderate chordee 3 + + Glanular Mild chordee 4 + + Proximal Significant chordee 5 + + Proximal Severe chordee 6 + + Glanular Undescended testes 7 + + Proximal Undescended testes 8 + + Proximal Severe chordee 9 + + Proximal Bifid scrotum 10 + + Distal None 11 + + Distal Mild chordee 12 + + Proximal Mild chordee 13 + + Proximal Bifid scrotum 14 + + Proximal Severe penoscrotal transposition 15 + + Proximal Marked chordee 16 + + Proximal Penoscrotal transposition 17 + + Not documented None 18 + + Not documented None 19 + − NA Penopubic epispadias 20 + − NA None 21 + − NA Bladder exstrophy 22 + − NA Mild penoscrotal transposition 23 + − NA None 24 + − NA None 25 + − NA None a + or − refers to whether or not the patient was diagnosed with hypospadias. b The Hadidi classification system was used[4] .